Sharia and Non-Sharia Firms: Analysis on the Dividend Policy of Indonesian Companies - Tyas, Luluk Ayuning; Bandi, Bandi (Universitas Pendidikan Indonesia, 2021)
The development of the capital market in Indonesia has prompted companies to issue sharia stocks which have an impact on the company's fundamental policies, one of which is the dividend policy. This study aims to determine the effect of sharia compliance, managerial ownership, institutional ownership, and gender diversity on dividend policies in manufacturing companies listed on the Indonesia Stock Exchange and included in the Indonesia Sharia Stock Index during the 2014-2019 period. The population in this study was 217 companies. The sampling method used a purposive sampling method, based on certain criteria and the final sample was 190 companies, so there were 1140 observational data in this study. The data used in this research was secondary data from the Indonesia Stock Exchange website (www.idx.co.id). The data analysis technique in this study used logistic regression model. The results of this study indicated that sharia compliance and managerial ownership had a significant negative effect on dividend policy, while institutional ownership and gender diversity had no significant effect on dividend policy